1996
DOI: 10.1111/j.1528-1157.1996.tb00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of L‐Carnitine Supplementation on Acute Valproate Intoxication

Abstract: We analyzed urinary valproate (VPA) metabolites and carnitine concentrations in a child who accidentally ingested 400 mg/kg VPA. The concentration of 4-en VPA, the presumed major factor in VPA-induced hepatotoxicity, was markedly increased, without liver dysfunction or hyperammonemia. The other major abnormality was decreased beta-oxidation and markedly increased omega-oxidation. After L-carnitine supplementation, VPA metabolism returned to normal. The level of valproylcarnitine was not increased and therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(31 citation statements)
references
References 9 publications
0
29
0
2
Order By: Relevance
“…Ishikura et al and Murakami et al each presented a case in which the administration of L-carnitine increased the metabolism of VPA via ␤-oxidation by passing the -oxidation and the production of the toxic metabolite [36,40]. Another study showed that supplementing L-carnitine in epileptic children with two or more risk factors for developing functional carnitine deficiency may be beneficial.…”
Section: How Do You Manage Patients With Valproic Acid Toxicity?mentioning
confidence: 99%
See 3 more Smart Citations
“…Ishikura et al and Murakami et al each presented a case in which the administration of L-carnitine increased the metabolism of VPA via ␤-oxidation by passing the -oxidation and the production of the toxic metabolite [36,40]. Another study showed that supplementing L-carnitine in epileptic children with two or more risk factors for developing functional carnitine deficiency may be beneficial.…”
Section: How Do You Manage Patients With Valproic Acid Toxicity?mentioning
confidence: 99%
“…They initially found large amounts of VPA -oxidation metabolites, but no metabolites from the ␤-oxidation pathway. However, when the patient received exogenous carnitine, significant amounts of ␤-oxidation metabolites were detected [40]. This led to the conclusion that carnitine depletion plays a significant role in the metabolism of the intermediary metabolites of VPA.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…They reported that serum ammonia levels declined more rapidly than resolution of VHE, and that glutamine levels or electroencephalogram appeared to be better correlated with resolution of VHE than ammonia level. In case reports by Murakami et al and Ishikura et al, the patients remained comatose for 3 to 4 days despite early initiation of L-carnitine treatment (6,7).…”
mentioning
confidence: 99%